2018
DOI: 10.1017/s1755773918000115
|View full text |Cite
|
Sign up to set email alerts
|

Punctuated equilibrium in democracy and autocracy: an analysis of Hungarian budgeting between 1868 and 2013

Abstract: The article investigates the dynamics of budgeting and its explanatory factors in Hungary based on a new database. Previous work for the period between 1991 and 2013 demonstrated that year-on-year changes in budgetary allocations by policy topics show a leptokurtic distribution. This distribution of policy changes is generally associated with the notion of punctuated equilibrium. We extend this analysis to cover over 155 years of Hungarian budgetary history. Our investigation of a database of 2580 spending cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…We coded thousands of documents produced by these venues to generate 11 series of yearly policy priorities during the Hu and Xi administrations. Consistent with widely applied procedures (see Jones & Baumgartner, 2005; Baumgartner et al, 2009; Baumgartner et al 2017; Jones et al, 2009; Sebők & Berki, 2018), each data point is categorized into discrete policy topics. Our analysis follows the official policy classification where feasible.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…We coded thousands of documents produced by these venues to generate 11 series of yearly policy priorities during the Hu and Xi administrations. Consistent with widely applied procedures (see Jones & Baumgartner, 2005; Baumgartner et al, 2009; Baumgartner et al 2017; Jones et al, 2009; Sebők & Berki, 2018), each data point is categorized into discrete policy topics. Our analysis follows the official policy classification where feasible.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Yet, when it comes to another region with a turbulent past and multiple regimes changes, Central and Eastern Europe (CEE), similar studies are few and far between (for two exceptions see (Boda and Patkós 2018;Sebők and Berki 2018). In light of this gap in the literature, the dual purpose of this article is to conceptualise policy dynamics for settings beyond liberal democracy and to extend the external validity of previous research on policy dynamics both in a geographical and historical sense.…”
Section: Introductionmentioning
confidence: 93%
“…We undertake this challenge by investigating four hypotheses derived from the relevant literature. We first test three hypotheses originally formulated by Baumgartner et al (2009: 608-609) and Baumgartner, Carammia, Epp, Noble, Rey, and Yildirim (2017), as well as a fourth one based on Sebők and Berki (2018).…”
Section: Theorymentioning
confidence: 99%
“…If so, one would expect higher policy instability in autocracies. Indeed, both Baumgartner et al (2017) and Sebők and Berki (2018) found that policy punctuations are higher in autocracies.…”
Section: Contentmentioning
confidence: 99%
“…By procedures and actors we describe formally or informally institutionalized processes that channel policymaking from agenda-setting throughout the whole policy cycle; the venues that provide policy actors access to the process; and the number and composition of policy actors having an influence on policy outputs and outcomes. Procedures employed under different regimes have spurred less academic interest than the content of policies until recently when a number of publications have treated the issue from different angles (Bartha et al, 2020;see Baumgartner et al, 2017;Boda & Patkós, 2018a;Guy & Jon, 2019;Howlett & Tosun, 2019;Sebők & Berki, 2018).…”
Section: Procedures and Actorsmentioning
confidence: 99%